Case study: recombinant Bromelain cloning, characterization and upstream processes - Amid, Azura; Ismail, Nurul Azira; Jamaluddin, Mohd Jamil Aizat (Springer International Publishing, 2015)
This chapter presents the recombinant stem bromelain cloning procedure followed by its characterization and finally upstream processing. Most of the procedures had patents filed in Malaysia, Europe and the United State of America with application numbers PI 20095434, 10015711.4, and 12968766, respectively. Portions of the experimental procedures were also presented in our publication (Amid et al., Process Biochem 46:2232–2239, 2011). The entire cloning process, characterization and the upstream processing of the recombinant bromelain production are briefly explained.